2020
DOI: 10.3389/fmicb.2020.00445
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Succession and Chemical Composition Involved in the Radish Fermentation Process in Different Containers

Abstract: Traditional Chinese fermented vegetables are a type of brine-salted fermented vegetable product. During the spontaneous fermentation, various compounds are produced, degraded, and converted, influencing the quality of the fermented pickle. To ascertain the effect of different containers on the fermentation process of the pickles, this study investigated the bacterial diversity and the chemical composition characteristics of the pickle (radish) fermented in commonly used containers including glass jars (GL), po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Aldehydes are considered the key flavor compounds in fermented vegetables with sweet, fruity, nutty, and caramel-like odors, which are produced by unsaturated fatty acids oxidation and amino acids catabolism (Liu et al, 2020). In addition, aldehydes can also be reduced to the corresponding alcohols or oxidized to the corresponding acids (Zhao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Aldehydes are considered the key flavor compounds in fermented vegetables with sweet, fruity, nutty, and caramel-like odors, which are produced by unsaturated fatty acids oxidation and amino acids catabolism (Liu et al, 2020). In addition, aldehydes can also be reduced to the corresponding alcohols or oxidized to the corresponding acids (Zhao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the average content of 4-hydroxytoluene (P2) reached 205.41 μg/kg in JX samples. According to previous reports, phenols are responsible for smoky and phenolic odors ( Liu et al, 2020 ). Therefore, phenols can provide a unique flavor for Xuecai produced in JX.…”
Section: Resultsmentioning
confidence: 96%
“…This study confirmed that some Leuconostoc species are involved in mannitol production, due to negative correlation with fructose and positive correlation with mannitol and acetic acid ( 36 ). Lactobacilli and Pediococcus species resulted the main producers of lactic acid, as showed by the strong positive correlation, with glucose and fructose as the major fermentable sugars consumed by them ( 9 , 37 , 38 ). The negative correlation between lactobacilli and Pediococcus species and phenolic acids was related to their capability to metabolize hydroxycinnamic acids, which are precursors of phloretic and dihydroferulic acids ( 15 , 18 , 39 ).…”
Section: Discussionmentioning
confidence: 95%